IoT-Based Irrigation Control System with ESP32 for Sustainable Agriculture - Nazwa Amelia Purnama; Rafif Abyakto; Muhammad Gilang Nur Rosyid; Danna Rayyana Irfawan; Muhammad Soli; Didik Aribowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The global food crisis has become one of the most pressing issues requiring serious attention, especially as the world's population continues to grow. This growth has led to an increasing demand for food, while agricultural resources such as fertile land, water, and labor become increasingly limited. These conditions present significant challenges for farmers, including droughts that damage crops, floods that devastate agricultural lands, and pest attacks that significantly reduce yields. Furthermore, global climate change exacerbates the situation, directly impacting the stability of food production. Unpredictable weather patterns threaten harvest success, increase the risk of crop failure, and decrease agricultural productivity. Therefore, innovative solutions, such as utilizing Internet of Things (IoT)-based technologies, are urgently needed to support the sustainability of the agricultural sector by enhancing efficiency, effectiveness, and global food security. This study aims to contribute to addressing these challenges through a modern technological approach